Sinonasal disease among patients with primary ciliary dyskinesia: an international study. - ERDEM ERALP, ELA (My University, 2023)
Background Sinonasal symptoms are a common feature of primary ciliary dyskinesia (PCD); however, literature about their severity and frequency, particularly during the life course, is scarce. Using baseline data from the Ear, nose and throat (ENT) Prospective International Cohort of PCD patients, we describe sinonasal disease in PCD. Methods We included participants who had a routine sinonasal examination during which they completed a symptoms questionnaire. We compared frequency of reported symptoms and examination findings among children and adults, and identified characteristics potentially associated with higher risk of sinonasal disease using ordinal regression. Results 12 centres contributed 384 participants; median age was 16 years (IQR 9–22), and 54% were male. Chronic nasal problems were the most common feature, reported by 341 (89%). More adults (33; 24%) than children (10; 4%) described hyposmia. Quality of life was moderately affected by rhinosinusitis among 136 participants with completed SNOT-22 questionnaires (median score 31; IQR 23–45). Examinations revealed nasal polyps among 51 of 345 participants (15%) and hypertrophic inferior nasal turbinates among 127 of 341 participants (37%). Facial pain was detected in 50 of 342 participants (15%). Nasal polyps, hypertrophic turbinates, deviated septum and facial pain were found more commonly in adults than children. The only characteristic associated with higher risk of sinonasal disease was age 10 years and older. Conclusions Based on our findings, regular sinonasal examinations are relevant for patients with PCD of all ages. There is a need for improved management of sinonasal disease supported by evidence-based guidelines.